Implementing the Cooperative Learning Model to Foster Cooperation Skills in Pancasila Learning among Elementary School Students - Irwan Irwan; Manan Manan; Faslia Faslia (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to determine the extent to which the implementation of the Cooperative Learning model can develop cooperative attitudes in Pancasila learning in the fourth grade at Public Elementary School 1 Katobengke. The method used is qualitative research with a descriptive qualitative approach. The results indicate that students’ cooperative attitudes have been well established and effectively carried out, and the implementation of the Cooperative Learning model has a positive impact on improving students’ quality in working together. Additionally, cooperative learning significantly contributes to fostering students’ collaborative character with greater enthusiasm. Its implementation in the classroom includes presenting learning objectives, explaining the material, forming groups, completing group tasks, presenting group work, providing feedback, and giving rewards. Furthermore, through this model, students gain more meaningful learning experiences and develop concern for their peers, thereby training their ability to respond quickly and appropriately within the group.